A wide linearity range and high sensitivity flexible pressure sensor with hierarchical microstructures via laser marking. Issue 9 (31st January 2020) - Li, Zhaoyang; Zhang, Bo; Li, Kun; Zhang, Tong; Yang, Xiaoniu
Abstract : The performance of a hierarchical microstructure-based flexible pressure sensor with a wide linearity range and high sensitivity, and the applications of the flexible pressure sensor for human activities. Abstract : Developing high sensitivity and broad linearity range flexible pressure sensors has become a key challenge in the field of human–machine interfaces, health monitoring, and electronic skin (E-skin). Here, we proposed a simple, customizable, and low-cost method to construct novel hierarchical microstructures via a laser marking technique, and we achieved a flexible pressure sensor with high performance. Our pressure sensor based on the novel hierarchical microstructures showed a high sensitivity of 15.4 kPa −1 in a broad linearity range over 200 kPa. The sensing performances were greatly enhanced when compared with the regular hemispherical microstructure-based pressure sensors. Note, the high sensitivity over a wide linearity range was one of the best results for the flexible pressure sensors so far. The mechanism of the sensors was further revealed by in situ observation. The contact area of the hierarchical microstructure arrays varied linearly with the pressure in a much wider range than that of the regular hemispherical arrays, which was in accordance with their sensing performances. Moreover, the sensor could test various physiological signals of the human body in a fast and stable way, including voice, pulse, hand gesture, and plantar pressure. Based on these advantages, our sensor exhibited great application potential in human–machine interfaces, health monitoring, and E-skin.